Innovations in Parental Involvement for Educational Improvement: A 2020–2025 Evidence Synthesis - Rindu Natasha Pamungkas; Lenny Nuraeni; Sri Nurhayati; Md Hafizi Ahsan; Sameer Mohammed Majed Dandan (Universitas Muhammadiyah Mataram, 2025)
Parental involvement is widely recognized as a key determinant of children’s academic achievement, motivation, and socio-emotional development, yet empirical evidence on concrete and scalable strategies remains fragmented. This study addresses this gap by conducting a structured literature review of 63 Scopus-indexed articles published between 2020 and 2025, focusing on empirical, English-language studies in primary and secondary education. A structured coding framework and data-extraction matrix served as the main research instruments, and thematic synthesis combined with descriptive mapping was used to analyze patterns, mechanisms, and contextual differences. Findings converge into five clusters of innovation: programmatic interventions, technology-enabled access, multi-channel communication systems, shared governance, and targeted outreach. Across these clusters, three cross-cutting mechanisms emerged capability building, relationship infrastructure, and cultural–contextual alignment which provide conceptual coherence and help explain why particular strategies succeed in different settings. The study’s contribution lies in offering a theoretically informed synthesis that links post-2020 innovations to established frameworks on family–school partnerships, including Epstein’s overlapping spheres of influence, Bronfenbrenner’s ecological systems theory, and the CAPE model of engagement. Practically, the review highlights low-cost, contextually sensitive strategies that schools can adopt to strengthen parent–school partnerships, from parenting programs and structured communication routines to inclusive governance structures and culturally responsive outreach. Policy implications include the need to invest in equitable digital access, systematic communication infrastructures, and mechanisms that position families as active partners in decision-making. Overall, the review provides an integrated roadmap for institutionalizing more equitable and sustainable parental engagement in education.